The Role of Natural Science in HRM at Industry 4.0 Era - Didik Hadiyatno; Dwi Taufik Rohman; Tutik Yuliani; Wiwik Saraswati (Postgraduate, University of Mataram, 2024)
Natural sciences—particularly psychology and biology—can be applied to better understand human behavior, cognitive processes, stress responses, and other factors influencing workplace dynamics and employee well-being. Natural science relies on empirical evidence gathered through observation, experimentation, and data analysis. It aims to formulate theories and laws that explain the natural world and predict future outcomes. The emergence of Industry 4.0 has transformed the landscape of Human Resource Management (HRM) by introducing advanced technologies, including artificial intelligence (AI), machine learning, and big data analytics. These innovations have enhanced HRM processes such as recruitment, training, performance evaluation, and employee engagement. Natural sciences play a critical role in understanding the dynamics of these technological advancements, offering insights into human behavior, cognitive processes, and organizational ecosystems. This article explores how principles of natural science, including biology, psychology, and neuroscience, integrate with modern HRM practices in the 4.0 era. Through a qualitative approach, we examine case studies to illustrate the application of natural science in HR strategies, highlighting the advantages and challenges of adopting a scientifically-informed HRM framework.